Psychological distress in corticosteroid-naive patients with systemic lupus erythematosus: A prospective cross-sectional study. (April 2016) - Nishimura, K; Omori, M; Katsumata, Y; Sato, E; Kawaguchi, Y; Harigai, M; Yamanaka, H; Ishigooka, J
Objective: Psychological distress, such as depression and anxiety, has been intensively studied in patients with systemic lupus erythematosus (SLE). However, those studies have mostly included patients who were treated with corticosteroids, which might themselves induce mood disturbances. We investigated psychological distress in corticosteroid-naive patients with SLE who did not exhibit any overt neuropsychiatric manifestations. Methods: Forty-three SLE in-patients with no current or past abnormal neuropsychiatric history participated in the study. Patients and 30 healthy control subjects with similar demographic and personality characteristics were administered a comprehensive battery of psychological/neuropsychological tests. The Profile of Mood States (POMS) was used to assess depression and anxiety. Results of clinical, laboratory, and neurological tests were compared with regard to their presence. Results: Prevalence of depression was higher in patients ( n = 11, 25.6%) than in controls ( n = 2, 6.7%; p = 0.035), although prevalence of anxiety did not differ across groups (patients: 34.9%, n = 15; controls: 16.7%, n = 5; p = 0.147). Using multiple logistic regression analysis, we identified avoidance coping methods (OR, 1.3; 95% CI 1.030–1.644; p = 0.027) as an independent risk factor for depression. Conclusion: Our results indicate that depression presents more frequently in corticosteroid-naive patients with early-stage, active SLE than in the normal population, but anxiety does not. Depression may be related to psychological reactions to suffering from the disease.